Study of antioxidant and cytotoxic activities of bioactive compounds of isolated actinomycetes From dholai bandar - M. A. TANDEL,; S. R. MAURYA,; R. G. DESAI, (International Journal of Pharma and Bio Sciences, 2017)
Actinomycetes are wide spread in nature and are virtually unlimited sources of novel bioactive compounds with many therapeutic applications. In the present study, we reported Antioxidant and Cytotoxic activities of bioactive compounds of isolated Actinomycetes. Total 6 marine Actinomycetes were isolated from five marine soil and five marine water sample of Dholai Bandar area of Valsad District, Gujarat, India. The isolates were tested with standard biochemical test and utilization of carbon sugar, to confirm the Actinomycetes. Metabolites Produced by using starch casein agar medium on shaker at 100 rpm within incubation periode 5-7 days at temperature 28ËšC.The antioxidant activity of the isolates was showed that metabolites of ethyl acetate extracts have higher reducing power than metabolites of ethyl alcohol extracts. Among tested extracts, those of Actinomycetes strain W19 shows highest reducing power with absorbance of about 1.0. The invitro cytotoxicity assay on yeast Saccharomyces cerevisiae cell revealed that the secondary metabolites had the strongest cytotoxicity with Ic50 7.46μg/ml. The data from both assays showed that marine Actinomycetes can be used as the potential source of natural antioxidant and cytotoxic compounds.